Physical and Chemical Conditions of Bayur Bay Waters On the East and West Season - Ulung Jantama Wisha; Try Al Tanto; Ilham Ilham (Marine Science Department Diponegoro University, 2017)
Physical construction of Bayur bay coastal area as a port was followed by a variety of environmental issues, both physical degradation of the natural environment, biology reduction and an increase in social problems, directly affect to water quality decreasing in the coastal Bayur Bay. This study aims to determine the concentration distribution of physical and chemical parameters and their influence to water conditions on the east and west season. The method used is descriptive method (data taken by in situ and laboratory analysis), determining the location of sampling points based on purposive sampling method and tide prediction by NAOtide software. The results of field survey and laboratory measurements analysed using statistical method. The speed of sea currents on the east season ranged from 3,48 to 24,9 cm.s-1, while in the West season flow rate ranged from 1,4 to 57,7 cm.s-1. Rainfall in East Season ranged from 0-45 mm and The intensity of rainfall in West Season ranged from 0-30 mm. Sea-surface temperatures in the Eastern season range between 26,2- 31.5 °C, while in the west season SST range from 24,3 to 30,5°C. Dissolve oxygen concentration in the east season range from 4,3 to 6,1 mg.L-1, while the west monsoon conditions range from 4,1 to 6,4 mg.L-1. The pH values ranged from 7,4 to 8,1 in the Eastern season and ranged from 7,12 to 8,27 in the West season. Bayur Bay water quality conditions is not much different from its value range on the west and east season and influencing each other. Keywords: Bayur Bay, Seasons, SST, Statistical method